Rethinking human development security for the future : 5th National Conference of the Southeast Asian Association for Gender Studies, Malaysia Branch (SAMA), 4th September 2004, Hotel Marriot, Putrajaya - National Conference of the Southeast Asian Association for Gender Studies, Malaysia Branch 2004 : Putrajaya); Zaharah Hassan; Bahiyah Dato' Haji Abdul Hamid; Jamilah Mustafa; Southeast Asian Association for Gender Studies, Malaysia Branch; Universiti Kebangsaan Malaysia. Pusat Pengembangan Gender ([Bangi] : Southeast Asian Association for Gender Studies, Malaysia Branch, 2004)
Contained paper works and kernote address for the conference on rethinking human development
Proceeding publication in association with COLLA Research Team, UPM
Keywords: Human ecology -- Congresses; Social problems -- Congresses; International cooperation -- Social aspects -- Congresses; Globalization -- Social aspects -- Congresses